The analysis of financial inclusion and its determinants in the rural area of south Wollo zone, Amhara Region, Ethiopia - Tefera Getachew Dagnachew; Temeselew Woldetsadik Mawugatie (Cogent Economics & Finance, 2022)
The main goal of this study is to examine financial inclusion and related factors in rural South Wollo Zone areas. The binary logit model, primary and secondary data, and multi-stage sampling techniques were all applied in the study. Only 20.72 percent of those questioned in the rural South Wollo zone were given access to formal financial institutions, leaving 79.28 percent of those who were excluded. According to the report, access to traditional financial institutions is influenced favorably by factors such as affordability, financial literacy, age, and secondary education in rural areas, as well as the availability of Islamic banking services. Both the inability of rural inhabitants to access formal financial institutions and their lack of trust in traditional financial institutions represent significant obstacles. The study also looks into the expensive replacement of formal financial institutions in rural areas by traditional financial groups. Based on our research, we recommend that the government and other relevant organizations seek to improve the country's degree of financial inclusion in rural areas by offering formal financial services at a reasonable cost and by boosting the financial capacity of rural low-income groups.
Keywords: 330; binary logistic model; development and rural area; financial inclusion